HUBUNGAN PERILAKU MEMILIH PEREMPUAN DENGAN KETERPILIHAN CALON BUPATI PEREMPUAN PADA PILKADA SERENTAK DI KABUPATEN KOTAWARINGIN BARAT TAHUN 2017 - Pratama, Danhes Eugene; Adnan, Muhammad (Journal of Politic and Government Studies, 2018)
One of the principles of democracy is political equality. This form of participation in political participation involves all citizens regardless of gender, ethnicity, religion, or certain social groups. All citizens have the right to use the right to participate in political activities. The phenomenon of the election of Hj. Nurhidayah, S.H., M.H. as the winner in the simultaneous local election has become a remarkable history for West Kotawaringin Regency as Hj. Nurhidayah, S.H., M.H. will be the first woman Regent. Correlation between Women’s Voting Behaviour and the Election of Women Regent Candidates in Simultaneous Local Election in West Kotawaringin Regency 2017 aims to find out whether or not there is a correlation between women's voting behaviour and the election of women Regent candidates, considering that the elected Regent candidates is the first female Regent, and from demographic and political participation aspects, female voters in West Kotawaringin Regency are quite high. This study uses a type of expanatory research with a quantitative approach. The theory used in this study is the theory of voting behaviour using two approaches namely sociological approach and rational choice approach. The statistical test tool used in this study is the contingency coefficient test by giving questionnaires to 100 female voters randomly selected in West Kotawaringin Regency. Based on the research that has been done, there is a correlation between women's voting behaviour and the election of women Regent candidates in simultaneous elections in West Kotawaringin Regency, especially educational factors and assessment of work programs / vision and mission. Female voters with higher education tend to choose women Regents and the assessment of the work program /vision becomes the basis for choosing the dominant female voters in choosing.Keywords: Voting behaviour, Gender, Election